Cold Dense Ion Outflow Observed in the Martian‐Induced Magnetotail by MAVEN. Issue 11 (5th June 2018) - Inui, S.; Seki, K.; Namekawa, T.; Sakai, S.; Brain, D. A.; Hara, T.; McFadden, J. P.; Halekas, J. S.; Mitchell, D. L.; Mazelle, C.; DiBraccio, G. A.; Jakosky, B. M.
Abstract: Cold ion outflow is one of the candidate processes to cause significant atmospheric escape from Mars. We here report on the cold dense heavy ion outflow event observed in Martian‐induced magnetotail by Mars Atmosphere and Volatile EvolutioN (MAVEN) on 4 December 2014. In the outflow event, the cold dense heavy ion outflow was observed only in south dusk downward convection electric field (E) lobe. During the event, the strong crustal magnetic field was located on dayside of Mars. It suggests that combination of minimagnetosphere and downward E facilitates the cold dense heavy ion outflow. In order to estimate the CO2 + density, we adopted a fitting method of log‐normal distribution to the O2 + time of flight distributions to eliminate O2 + contamination in the CO2 + time of flight data. Contribution of O2 +, O +, and CO2 + to the total heavy ions (~134 cm −3 ) is about 71%, 26%, and 3%, respectively. Average heavy ion flux was ~5.4 × 10 7  cm −2 s −1, assuming the escape velocity at 2, 000‐km altitude. Plain Language Summary: Mars has a cold surface temperature and little water on surface at present. However, it is thought that Mars had a warm climate and liquid water on surface about 4 billion years ago. In order to cause the climate change, a large amount of CO2, that is, greenhouse gas, needs to be removed from Martian atmosphere. While the ion escape from the Martian upper atmosphere to space through interaction between the solar wind and Mars is one of the candidate mechanisms to remove CO2, detailed characteristics of the ion escape such as its composition and relation to the solar wind conditions are far from understood. Based on observations in the Martian‐induced magnetotail by the Mars Atmosphere and Volatile EvolutioN mission, we here report on the cold dense heavy ion outflow event which accounts for a significant escape flux. A careful analysis enables us to derive densities of O +, O2 +, and CO2 + ions separately. The resultant ion species ratio suggests the ion escape from deep ionosphere below altitudes of 300 km. Observations also indicate that both the solar wind electric field and the crustal magnetic fields play an important role to cause the cold dense ion outflow. Key Points: Cold dense heavy ion outflow was observed by MAVEN in the southern downward E SW quadrant of the Martian‐induced magnetotail CO2 + number density estimated by a fitting method to eliminate O2 + contamination accounts for about 3% of the total heavy ion outflow The ratio of O2 + :O + :CO2 + suggests that the source altitude of heavy ion outflow was around 260 km or below in the Martian ionosphere